Diagnosis of components passionarity: presentation techniques - Kuznetsova, Oxana (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2017)
The paper presents the results of the stages of development and testing of psychodiagnostic techniques designed to study the components passionarity. Рassionarity considered as individual susceptibility to transformation of reality (changing environment) aimed at implementing sustainable functional purpose in solving existential problems. The structure and components passionarity. Individual values and their totality reflecting the specific passionarity personality, allowing to identify in adults as dominant orientation in establishing authentic I (solving existential problems), and the trends of social behavior personality. Testing of psychodiagnostic methods carried out according to the requirements psyhometry. Results of the audit methodology on reliability, validity and dyskryminatyvnist suggest its psycho effective tool designed to study passionarnosti.